Is value investing based on scoring models effective? The verification of F-Score-based strategy in the Polish stock market - Pilch Bartłomiej (Economics and Business Review, 2023)
The aim of the paper is to analyse the effectiveness of F-Score-like models using the example of the Polish stock market. F-Score is a scoring model based on a high B/M investing strategy, which uses fundamental signals to assess the economic condition of an entity. So far, its effectiveness has been generally proven in numerous stock markets worldwide. However, no comprehensive study focusing on the Polish market has been conducted. Therefore, F-Score and similar models (FS-Score and PiotroskiTrfm) were analysed in this regard. It was shown that companies with higher scores generated positive both raw and market-adjusted returns on average. However, they were lower than the mean returns of low-score companies (for FS-Score) or total high B/M portfolio (regarding F-Score and PiotroskiTrfm). The results of the study show that F-Score, FS-Score and PiotroskiTrfm are generally effective investing tools. However, it might be more advisable for value investors to choose a total high B/M portfolio instead of shares of high-score entities according to F-Score or PiotroskiTrfm.